Dynamics of the Morphological Changes in the Progo River Due to Lahar Transport from Merapi Volcano - Adhitama, Adib Prima; Jatmiko, Retnadi Heru; Mei, Estuning Tyas Wulan; Sartohadi, Junun (Faculty of Geography, Universitas Gadjah Mada, 2024)
The Merapi eruption in 2010 and 1975 caused lahar floods on the Progo River segment in Kulon Progo. This study aims to analyze the dynamics of river morphology changes that are affected by two lahar floods. Temporal images representing the two lahar flood events up to several years later were used to see river morphology changes. Temporal data from remote sensing and UAV is able to indicate the morphological change of river valleys in the study area. The analysis was carried out based on the parameters of river slope, riverbank morphology, and river curvature. The river slope is 0.74% which means the slope is flat. This condition gives a consequence of the river's meandering morphology. The morphology of the riverbank has the